Patellofemoral joint kinetics in females when using different depths and loads during the barbell back squat - Zavala, L.; Flores, V.; Cotter, J. A.; Becker, J. (European Journal of Sport Science, 2021)
Back squats are a common strengthening exercise for knee and hip musculature. However, repetitive loaded movements like backs squats result in high patellofemoral joint loading and therefore may contribute to the development of common overuse injuries. Thus, it is important to understand how changing parameters such as squat depth or load influences patellofemoral loading. This study investigated differences in patellofemoral loading when experienced female lifters squatted to three depths (above parallel, parallel, and below parallel) and with three loads (unloaded, 50%, and 85% of depth-specific one repetition maximums). Patellofemoral joint reaction forces (pfJRF) and stresses (pfJS) were calculated from biomechanical models incorporating knee extensor moments (KEM) and joint angles. Peak KEMs displayed a depth-by-load interaction such that within each depth, as load increased so did peak KEM. However, within each load, the effects of depth were different. Peak pfJRF also increased with load and was higher at below parallel than above or parallel depths. Peak pfJS also displayed a depth-by-load interaction, increasing with load within a given depth, and being greatest at the below parallel depths within a given load. If patellofemoral joint loading is a concern, clinicians or coaches should carefully monitor the depth and load combinations being used.